Sustainable intensification in the production of grass and forage crops in the Low Countries of north‐west Europe. (19th February 2017) - Reheul, D.; Cougnon, M.; Kayser, M.; Pannecoucque, J.; Swanckaert, J.; De Cauwer, B.; van den Pol‐van Dasselaar, A.; De Vliegher, A.
Abstract: Production of grass and fodder crops in areas under intensive production systems in the Low Countries of north‐west Europe faces a number of threats related to increased regulations, scarcity of land and restricted freedom of use of the land, and from climate change. Grassland‐based farmers are pushed to do more with less, i.e., to improve eco‐efficiency, and this requires "more knowledge per ha." This article argues that progress in variety breeding, the application of crop rotation instead of monocultures, a proper use of catch crops, ley‐arable farming and overall good management offer realistic opportunities to cope with current threats. A large capacity for mechanization also allows improvement of net yields per ha. This article highlights that progress in plant breeding has compensated for yield declines caused by nutrient‐input restrictions in forage maize ( Zea mays L.). Both forage maize and grass–clover can take advantages of ley‐arable farming, and crop rotation provides an insurance against the effects of low‐yielding years and a buffer for reduced nutrient inputs.